UPAYA MENINGKATKAN PENGUASAAN KOHESI DAN KOHERENSI DENGAN PENDEKATAN KONTEKSTUAL BERBASIS PRODUK PADA MATA KULIAH ANALISIS WACANA - Winarsih, Eni (Widyabastra, 2012)
The aims of this research are: (1) Describing and explaining the learning of folklore by using STAD method; (2) improving studentsâ ability in appreciation of folklore by using STAD method;Â (3)Â describingÂ theÂ difficultiesÂ thatÂ facedÂ inÂ improvingÂ studentsÂ appreciationÂ of folklore by using STAD method of students VII F SMP Negeri 11 Madiun.This subject of the research is students of class VII F SMP Negeri 11 Madiun. The object of the research is the using of STAD method in âBahasa dan Sastra Indonesiaâ learning process asÂ theÂ effortÂ toÂ improveÂ studentsâÂ abilityÂ appreciationÂ ofÂ folklore.Â DataÂ resourceÂ are:Â (1) informant;Â Â (2)Â Â placeÂ Â andÂ Â event;Â Â (3)Â Â documents.Â Â Â Â Â DataÂ Â collectingÂ Â techniqueÂ Â are:Â Â (1) observation; (2) deep interview; (3) questionnaire; (4) test. Data validity used is triangulation techniqueÂ consistÂ of:Â (1)Â dataÂ triangulation;Â (2)Â methodÂ triangulation;Â (3)Â informantÂ review. Data analysis is by using comparative descriptive technique and critics analysis technique.The result of the research shows that using Student Team Achievement Division (STAD) can improveÂ theÂ abilityÂ inÂ appreciationÂ ofÂ folkloreÂ ofÂ studentsÂ classÂ VIIÂ FÂ SMPÂ NegeriÂ 11 Madiun.Â ItÂ canÂ beÂ seenÂ fromÂ theÂ resultÂ ofÂ pretestÂ andÂ posttestÂ thatÂ conductedÂ duringÂ three cycles.Â Â Â AtÂ theÂ testÂ beforeÂ actionÂ theÂ numberÂ ofÂ studentsÂ gettingÂ scoreÂ moreÂ thanÂ KKMÂ (70, 00)Â areÂ 16Â studentsÂ (40,Â 00%)Â withÂ averageÂ scoreÂ isÂ 65,Â 55.Â AtÂ firstÂ cycleÂ theÂ numberÂ of students getting more than KKM improves be 21 students (52, 50%). The improvement equal 12,Â 50%.Â WhileÂ classÂ averageÂ scoreÂ 65,Â 57Â hasÂ notÂ reachedÂ KKM.Â AtÂ secondÂ cycle,Â the improvement is 27 students equal 67, 50% has reached KKM or improvement 15% from first cycle,Â withÂ theÂ averageÂ classÂ scoreÂ 68,925.Â ThisÂ improvementÂ hasÂ notÂ reachedÂ KKMÂ 70,Â 00 and class minimum score has not reached 75%. So the process is continued in to third cycle. AfterÂ testÂ inÂ thirdÂ cycleÂ theÂ numberÂ studentsÂ canÂ reachedÂ KKMÂ areÂ 35Â studentsÂ (87,Â 50%) withÂ theÂ classÂ averageÂ scoreÂ isÂ 73,525.Â AtÂ thirdÂ cycleÂ classÂ minimumÂ scoreÂ hasÂ beenÂ more than 75%Â and minimum ability score is 70.00.Â ItÂ can be conclude that the learning byÂ using STAD method can improve quality and result learning. It also can be improve students ability in appreciation of folklore. Key Words: appreciation folklore, Student Team Achievement Division (STAD)